PIANOVISION - An Augmented Reality Piano Platform - Reid, Zachary; Teixeira, João Marcelo (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais Estendidos do XXIV Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2022.227701, 2022)
PianoVision presents the best version yet of an educational piano app for Oculus Quest. Not only does it overlay notes onto the real piano using passthrough and hand tracking, but it also responds to user’s playing in real time through connections with MIDI-enabled keyboards.